2023
DOI: 10.1037/dev0001526
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of families formed through third-party assisted reproduction: Mother–child relationships and child adjustment from infancy to adulthood.

Abstract: The seventh phase of this longitudinal study investigated whether children born through third-party assisted reproduction experienced psychological problems, or difficulties in their relationship with their mothers, in early adulthood. The impact of disclosure of their biological origins, and quality of mother–child relationships from age 3 onward, were also examined. Sixty-five assisted reproduction families, including 22 surrogacy families, 17 egg donation families, and 26 sperm donation families, were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Data were drawn from the seventh phase of the UK Longitudinal Study of Assisted Reproduction Families ( Golombok et al , in press ; Golombok, 2021 ). Fifty sperm donation families, 51 egg donation families, 42 surrogacy families, and 80 natural conception families, all headed by heterosexual couples, were first visited when the target child was aged 1 year ( Golombok et al , 2004a , b ) and data were subsequently collected at age 2 years ( Golombok et al , 2005 , 2006a ), 3 years ( Golombok et al , 2006b ), 7 years ( Golombok et al , 2011 ), 10 years ( Golombok et al , 2013 ), 14 years ( Golombok et al , 2017 ), and 20 years ( Golombok et al , in press ). With the exception of a small number of egg donation and surrogacy families who had used known egg donors, the families had used clinic donors prior to the 2005 change in the law and had thus used anonymous donors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were drawn from the seventh phase of the UK Longitudinal Study of Assisted Reproduction Families ( Golombok et al , in press ; Golombok, 2021 ). Fifty sperm donation families, 51 egg donation families, 42 surrogacy families, and 80 natural conception families, all headed by heterosexual couples, were first visited when the target child was aged 1 year ( Golombok et al , 2004a , b ) and data were subsequently collected at age 2 years ( Golombok et al , 2005 , 2006a ), 3 years ( Golombok et al , 2006b ), 7 years ( Golombok et al , 2011 ), 10 years ( Golombok et al , 2013 ), 14 years ( Golombok et al , 2017 ), and 20 years ( Golombok et al , in press ). With the exception of a small number of egg donation and surrogacy families who had used known egg donors, the families had used clinic donors prior to the 2005 change in the law and had thus used anonymous donors.…”
Section: Methodsmentioning
confidence: 99%
“…Non-disclosure runs the risk of the child finding out accidently or at a later age, which has been associated with more negative feelings about donor conception, including feelings of anger, shock, and confusion ( Turner and Coyle, 2000 ; Jadva et al , 2009 ; Beeson et al , 2011 ). In contrast, finding out in the preschool years has been found to be associated with more positive mother–child relationships in adolescence ( Ilioi et al , 2017 ), and early adulthood ( Golombok et al , in press ), and can enable the information to be incorporated into the child’s sense of identity ( Rumball and Adair, 1999 ). Some donor conceived individuals born following anonymous or identity-release donation have been found to express curiosity about their conception ( Jadva et al , 2009 , Scheib et al , 2005 ; Rodino et al , 2011 ), which, for some, leads to seeking information about their donor and/or their donor siblings ( Macmillan et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of child psychological adjustment, children conceived using egg donation were found to be well-adjusted in the European Study of Assisted Reproduction Families at both time points (Golombok et al, 1999;Murray et al, 2006), although the egg donation sample comprised only 21 families at Phase 1 and 17 families at Phase 2. The U.K. Longitudinal Study of Assisted Reproduction Families showed that children and adolescents showed good psychological adjustment at all phases of the study, with no differences between groups, as assessed using the widely used Strengths and Difficulties Questionnaire (SDQ) from age three onward (Golombok et al, 2005(Golombok et al, , 2006(Golombok et al, , 2011(Golombok et al, , 2013(Golombok et al, , 2017(Golombok et al, , 2023. A survey of more than 700 British parents with 5-9 year olds conceived through five types of assisted reproduction found higher levels of conduct problems in egg donation children than in children conceived through IVF and sperm donation as rated by fathers, although scores were in the normal range and no differences were found in mother-report data (Shelton et al, 2009).…”
mentioning
confidence: 99%
“…Longitudinal data on egg donation families have come from two studies: the European Study of Assisted Reproduction Families (Golombok et al, 1999;Murray et al, 2006) and the U.K. Longitudinal Study of Assisted Reproduction Families (Golombok et al, 2004(Golombok et al, , 2005(Golombok et al, , 2006(Golombok et al, , 2011(Golombok et al, , 2013(Golombok et al, , 2017(Golombok et al, , 2023. The former compared outcomes for egg donation, sperm donation, adoptive, and IVF families at two time points, when children were aged 3-8 years and 12 years.…”
mentioning
confidence: 99%